The relationship between the atherogenic index of plasma and hyperuricemia in American adults aged over 20 years: A cross-sectional study - Chunjie She; Liuyang Shi; Yang Li; Linhan Qin; Nan Fang; Kehai Shi; Zhongping Miao; Hefeng Liu (PLoS ONE, 2026)
Background The presence of hyperuricemia (HUA) is closely associated with lipid disorders and the development of cardiovascular disease (CVD). However, research on the relationship between the atherogenic index of plasma (AIP) and HUA remains limited among the general adult population in the United States. This study aims to elucidate the association between the AIP and HUA using data from a nationally representative database in the United States. Methods This study included a total of 7,057 participants, with data obtained from the National Health and Nutrition Examination Survey (NHANES) spanning 2011–2018. The AIP was calculated as log10 (triglycerides/high-density lipoprotein cholesterol). HUA served as the outcome variable, defined by serum uric acid (SUA) levels. Multivariate logistic regression, generalized additive models, smoothing fitting curves, subgroup analyses, and interaction tests were employed to reveal the relationship between AIP and HUA. Results After adjusting for all covariates, a statistically significant positive correlation was observed between AIP and the odds of HUA (OR = 3.22, 95%CI [2.54, 4.10], P < 0.001). Participants in the highest AIP quartile (Q4) had a 1.76-fold higher risk of HUA compared to those in the reference AIP quartile (Q1) (OR = 2.76, 95%CI [2.20, 3.45], P < 0.001). Stratified analyses confirmed that the positive correlation between AIP and HUA risk was significant and consistent, regardless of gender and body mass index (BMI) category. Additionally, the study found a nonlinear inverted L-shaped association between AIP and the risk of HUA, with the inflection point at 0.34. Subgroup analysis revealed that gender had a significant interaction with the AIP. Females showed a stronger association than males. Conclusions AIP and the risk of HUA demonstrated an inverted L-shaped positive association in the adult US population. The association was stronger in females than in males.